2005
DOI: 10.1901/jaba.2005.118-04
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analyses of Caregiver Reprimands

Abstract: We conducted descriptive observations of 5 individuals with developmental disabilities and severe problem behavior while they interacted with their caregivers in either simulated environments (an inpatient hospital facility) or in their homes. The focus of the study was on caregiver reprimands and child problem behavior. Thus, we compared the frequency of problem behavior that immediately preceded a caregiver reprimand to that immediately following a caregiver reprimand, and the results showed that the frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 25 publications
8
51
0
Order By: Relevance
“…These results were similar to those of Sloman et al (2005), who found that reprimands were followed by a temporary decrease in problem behavior. It is possible that the temporary decrease in inappropriate mealtime behavior following reprimanding, coaxing, showing concern, or comforting may reinforce parent responses, thereby explaining the reluctance of parents to cease engaging in these responses.…”
Section: Discussionsupporting
confidence: 90%
“…These results were similar to those of Sloman et al (2005), who found that reprimands were followed by a temporary decrease in problem behavior. It is possible that the temporary decrease in inappropriate mealtime behavior following reprimanding, coaxing, showing concern, or comforting may reinforce parent responses, thereby explaining the reluctance of parents to cease engaging in these responses.…”
Section: Discussionsupporting
confidence: 90%
“…Descriptive assessments have been used in a number of investigations to assess the relationship between care provider behavior and a variety of other behavior problems (e.g., Lalli, Browder, Mace, & Brown, 1993;Lerman & Iwata, 1993;Mace & Lalli, 1991;Sloman et al, 2005;Vollmer, Borrero, Wright, Van Camp, & Lalli, 2001). Pretreatment descriptive assessments may be useful for the treatment of food refusal in at least two ways.…”
mentioning
confidence: 99%
“…This study therefore adds to existing research into the effects of the interrelated programs, and is necessary for a complete understanding of development and generalization of behavior (Hanley, Iwata & McCord, 2003;Sloman et al, 2005). In summary, it´s therefore necessary to facilitate a constructive movement, defined as a related interactiveaffective approach, in order to facilitate improvement and intersubjective development of both one's own interests and feelings and also those of others, through a multimodal exchange process:…”
Section: Discussionmentioning
confidence: 99%